Датчики вимірювання кутового положення вала на базі обладнання National instruments з платою QNET-mechkit "датчики для мехатроніки" - Асмолова, Лариса Валеріївна; Аніщенко, Микола Васильович; Лобода, Катерина Юріївна (НТУ "ХПІ", 2019)
Розглядається застосування плати QNET "Датчики для мехатроніки" з освітньої платформою NI ELVIS II + при організації циклу лабораторних робіт з курсу "Основи мехатроніки". Методика виконання робіт розглядається на прикладах двох лабораторних робіт по вивченню датчиків кута оберту вала електродвигуна: енкодера і потенціометра. Для підвищення якості навчання студентів при проведенні експериментів забезпечується наочність і точність відповідності реальних датчиків.

The article presents the methodological aspects of solving studentis educational and cognitive action problems in the process of the course "Mechatronics Fundamentals" studying. The opportunity of cycle of laboratory work implementation on Equipment company NATIONAL INSTRUMENTS base is regarded as an effective source of modern educational technology realization. The implementation and realization order of laboratory works on studying sensors of the electric motor’s angle rotation shaft from the example of two works on measuring the angle rotation using anencoder and a potentiometer based on the QNET MECHKIT module. The use of virtual instruments QNET Mechatronics Sensors provides visibility and accuracy of compliance with real sensors when conducting experiments. Improving the quality of student’s education for carrying out laboratory work is assured by the ability of multivariate tasks realization.
Sensors of measurement of shaft rotation angle on the basis of equipment National instruments on the board QNET-mechkit "sensors for mechatronics"
Keywords: віртуальний прилад; датчик кута оберту вала; енкодер; потенціометр; virtual instrument; shaft angle sensor; encoder; potentiometer